2014
DOI: 10.1021/ac5027836
|View full text |Cite
|
Sign up to set email alerts
|

Ion-Transfer Voltammetry of Perfluoroalkanesulfonates and Perfluoroalkanecarboxylates: Picomolar Detection Limit and High Lipophilicity

Abstract: Here we report on ion-transfer voltammetry of perfluoroalkanesulfonates and perfluoroalkanecarboxylates at the interface between a plasticized polymer membrane and water to enable the ultrasensitive detection of these persistent environmental contaminants with adverse health effects. The ion-transfer cyclic voltammograms of the perfluoroalkyl oxoanions are obtained by using a ∼1 μm thick poly(vinyl chloride) membrane plasticized with 2-nitrophenyl octyl ether. The cyclic voltammograms are numerically analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 35 publications
4
42
0
Order By: Relevance
“…The bulk concentrations are maintained near the interface during the voltammetric transfer of an analyte ion, because the aqueous phase contains excess amounts of primary and secondary ions 16 and because the membrane is sufficiently thin. 5,7,18-20 Accordingly, the bulk concentrations of the ionophore in its free and complex forms, [L] and [L n x X z x ], respectively, can be used to define an overall formation constant, β n x , as βnnormalX=[normalLnnormalXnormalXznormalX][normalL]nx[XzX]m The mass balance of the ionophore is also given by using the bulk concentrations as LnormalT=[normalL]+nnormalI[LnIIzI]+nnormalJ[LnJJzJ] where L T is the total concentration of the ionophore. The membrane composition depends on the phase boundary potential across the membrane/water interface, which is externally controlled to drive the interfacial transfer of primary and secondary ions.…”
Section: Theorymentioning
confidence: 99%
“…The bulk concentrations are maintained near the interface during the voltammetric transfer of an analyte ion, because the aqueous phase contains excess amounts of primary and secondary ions 16 and because the membrane is sufficiently thin. 5,7,18-20 Accordingly, the bulk concentrations of the ionophore in its free and complex forms, [L] and [L n x X z x ], respectively, can be used to define an overall formation constant, β n x , as βnnormalX=[normalLnnormalXnormalXznormalX][normalL]nx[XzX]m The mass balance of the ionophore is also given by using the bulk concentrations as LnormalT=[normalL]+nnormalI[LnIIzI]+nnormalJ[LnJJzJ] where L T is the total concentration of the ionophore. The membrane composition depends on the phase boundary potential across the membrane/water interface, which is externally controlled to drive the interfacial transfer of primary and secondary ions.…”
Section: Theorymentioning
confidence: 99%
“…Recently, it was demonstrated that a double-polymer-modified electrode in combination with ITSV is a powerful platform to reach a nanomolar limit of detection (LOD) for ions [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Advances in the investigation and modelling of transfer processes across soft interfaces are challenging and valuable given their interest in biological and environmental sciences 1 and their applications in chemical analysis, electrocatalysis and liquid|liquid extraction, among other fields. [2][3][4] Electrochemical methods have been proven to be very suitable for the study of the transfer of ionic species, [5][6][7] providing electrochemical strategies as alternatives to solid electrode electrochemistry for electroanalytical determinations. Ion transfer processes are usually coupled to chemical reactions in solution, which must be detected and characterized in order to fully elucidate the transfer mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Half-wave potential of the first wave obtained in NPV under chemical equilibrium conditions when z 1 a z 2 and two well-defined signals are obtained F Faraday constant I Current response in NPV I (1) First wave obtained in NPV when two well-defined signals are obtained I (2) Second wave obtained in NPV when two well-defined signals are obtained Total limiting current in NPV under chemical equilibrium conditions (I lim,eq = I (1) lim,eq + I (2) lim,eq ) when two well-defined signals are obtained I (1) lim,eq Limiting current of the first wave obtained in NPV under chemical equilibrium conditions when z 1 a z 2 and two well-defined signals are obtained I (2) lim,eq Limiting current of the second wave obtained in NPV under chemical equilibrium conditions when z 1 a z 2 and two well-defined signals are obtained I 1 peak Peak current of the first signal obtained in dNPV when two well-defined signals are obtained…”
mentioning
confidence: 99%
See 1 more Smart Citation